An Application of Emotion Detection in Sentiment Analysis on Movie Reviews - Sagum, Ria Ambrocio (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research focus on the issue of accuracy for sentiment analysis. The researcher experimented on emotion detection result to be used in sentiment analysis. The emotions that were included in this research are happiness, sadness, anger, and fear. Once emotion was detected the system will then use it to know the sentiment of the person on a particular movie. This paper aims to measure the accuracy in sentiment analysis enhanced by emotion detection and to know whether emotion detection plays a key role in reading sentiment analysis.